ADAMPAK PENGAWASAN MELEKAT DAN MOTIVASI TERHADAP DISIPLIN KARYAWAN PT. KERETA API INDONESIA DIVISI REGIONAL TANJUNG KARANG - Zuriana -; Aditya Kurniawan (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2019)
This study aims to analyze the effect of adhering supervision and work motivation on the workdiscipline of the employees in operation division of PT. Kereta Api Indonesia (Persero) Wilayah BRegional Division IV Tanjung Karang. This type of research is quantitative research. The population inthis study was employees in operation division of the PT. Kereta Api Indonesia (Persero) Region BTanjung Karang Regional Division IV which numbered 95 employees and all populations were used assamples.Adhering supervision (waskat) and work motivation have a positive effect on employee workdiscipline both partially and simultaneously. The coefficient of determination R2 (R Squares) of 0.186shows that Work Discipline (Y) is influenced by Adhering Supervision (X1) and Work Motivation (X2) of18.6%.